Pediatric densitometry: is the Z score adjustment necessary in all cases? - Magallares, Berta; Malouf, Jorge; Codes-Méndez, Helena; Park, Hye Sang; Betancourt, Jocelyn; Fraga, Gloria; Quesada-Masachs, Estefanía; López-Corbeto, Mireia; Torrent, Montserrat; Marín, Ana; Herrera, Silvia; Gich, Ignasi; et al. (Frontiers in Endocrinology, 2025)
BackgroundThe International Society for Clinical Densitometry recommends adjusting the bone mineral density (BMD) Z-score in children with short stature or growth delay. However, it is not clear whether height-for-age Z-score (HAZ) adjustment is required in all children. The aim of this study was to determine whether HAZ adjustment is necessary by examining variability in unadjusted and adjusted Z-scores for the main regions of interest in a large pediatric cohort.MethodsWe evaluated 103 patients ≤ 20 years of age who underwent lumbar spine and whole-body dual-energy x-ray absorptiometry (DXA) at our tertiary care hospital from 2016 to 2018. The formula proposed by Zemel was used to calculate the HAZ.ResultsA total of 103 participants were included (54 females; 52.4%). The mean age was 9.8 years. Height percentiles were ≤ 3 or ≥ 97 in seven (6.8%) and five (4.9%) patients. Diagnostic criteria for low bone mineral density (LBMD; BMD Z-score ≤ −2) were met in 8 lumbar spine scans and 10 whole-body scans. After HAZ adjustment, the prevalence of LBMD decreased from 8.2% (n=8) to 6.4% (n=6) in the lumbar spine scans and from 10.5% (n=10) to 7.2% (n=8) in the whole-body scans. Agreement between the adjusted and non-adjusted HAZ data was 0.498 for the lumbar spine and 0.557 for the whole body. The diagnostic discrepancy rate for LBMD diagnosis was 7%. After HAZ adjustment, 5% patients no longer met LBMD criteria while conversely 2% met LBMD criteria only after adjustment.ConclusionsThe high diagnostic discrepancy rate (7%) for LBMN in this unselected pediatric cohort underscores the value of performing HAZ adjustment of Z-scores to improve diagnostic accuracy. This divergence between adjusted and unadjusted Z-scores suggests that all pediatric patients, not only those with short stature or growth retardation, may benefit from densitometric size adjustment. This is especially true in individuals whose stature is at the upper end of the range, where size may obscure a diagnosis of LBMD.